Determinasi Pola Konsumsi Minuman Keras pada Remaja di Pulau Lombok - MUSPARLIN HALID (Biota, 2017)
This study aims to identify the determinants of alcohol consumption patterns (liquor) in adolescents in Lombok Island, the condition of alcohol abuse that is already at a very alarming level. This research used cross-sectional design with quantitative approach. Sample taken by purposive sampling in juvenile Junior High School (JHS) and Senior High School (SHS) in Lombok Island amounted to 1664 students. Data collected by using questionnaires distributed to respondents. The variables measured as follows: alcohol consumption patterns, gender, age, cigarette consumption pattern, parental education level, parental divorce status, peer influence, social media influence, sexual behavior, conflict with spouses and family conflicts. Data analysis was descriptive and Chi-square with significant level p <0.05 and Odds Ratio (OR) with Confidence Interval (CI) 95%. There was a significant relationship between alcohol consumption (liquor) > 3 liter/week pattern in adolescents in Lombok Island based on gender, age, cigarette consumption pattern, parental education level, parental divorce status, peer influence, social media, sexual behavior, conflict with spouse and conflict with family (p <0.05). This can be concluded that the causality of alcohol consumption patterns (liquor) in adolescents was determined by various factors derived from the environment and internal factors within the adolescent. Thus, it is necessary to do promotive and preventive efforts in minimizing alcohol abuse in adolescents.